Dynamic modeling and thermodynamic analysis of lithium bromide absorption refrigeration system using Modelica - Zhou, Yujie; Pan, Lei; Han, Xu; Sun, Li (Applied thermal engineering, 2023)
•Dynamic model of single effect LiBr absorption chiller is developed with Modelica.•Energy and exergy analysis are conducted in steady-state simulation.•Dynamic responses of components and system are discussed in detail. Lithium bromide absorption refrigeration system (ARS) is promising in utilizing industrial exhaust heat and improving energy efficiency. ARS consists of a generator, absorber, condenser, evaporator, solution heat exchanger, pump, and valves. To better operate ARS in a changing environment, it is essential to conduct dynamic modeling and analysis, which might be challenging and cumbersome with conventional modeling tools. Object-oriented, acausal modeling language Modelica can effectively address the modeling limitations on this multi-domain energy system, which provides an opportunity for rapid prototyping and dynamic modeling. Therefore, a customized Modelica library for dynamic modeling of the single-effect lithium bromide ARS is developed. Specifically, the dynamics of the main components including the generator, absorber and heat exchangers are modeled based on the mass/energy/momentum conservation laws. To capture the alteration of the medium state, the finite volume method is adopted in the modeling of heat exchangers. The model is well-validated under on-design and off-design conditions. Then, energy analysis is conducted to find the optimal working point. The COP reaches the maximum value of 0.793 when hot/cold water flowrate is 0.9 m3/h and 3 m3/h. And exergy analysis supports the above analysis from the perspective of the second law. At last, dynamic responses of the hot/cold water flowrate/temperature are investigated. Dynamic simulation reveals the response rapidity of variables, strong coupling, and different transient trends (overshoot or initial inverse). Additionally, the maximum/minimum vapor quality at the evaporator/condenser outlet is 1.005/0.022.